Preparation method and application of magnesium flame retardant whisker containing multiple metal elements

By growing bimetallic hydroxide sheets on the surface of magnesium hydroxide whiskers, flame retardant synergistic agents containing a variety of metal elements are prepared, and the problem of low efficiency of traditional magnesium hydroxide flame retardant is solved, which significantly improves its flame retardant, smoke suppression and attenuation effects, and enhances the tensile strength of polymer composite materials.

CN119145032BActive Publication Date: 2025-03-18UNIV OF SCI & TECH OF CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411649244.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Traditional magnesium hydroxide flame retardants have low efficiency and require large amounts of addition to reach a certain flame retardant level, resulting in an increase in resin viscosity and a decrease in processing performance.

Method used

By growing bimetallic hydroxide sheets vertically on the surface of magnesium hydroxide whiskers, flame retardant synergists containing a variety of catalytically active metal elements are prepared to enhance their flame retardant, smoke suppression and attenuation effects.

Benefits of technology

The flame retardant, smoke suppression and attenuation effects of magnesium hydroxide whiskers are improved, the tensile strength of polymer composite materials is enhanced, and the transformation from low-value bitter halogen resources to high-value and high-performance flame retardants is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145032B_ABST
    Figure CN119145032B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a magnesium flame retardant whisker containing multiple metal elements and its application, belonging to the technical field of flame retardant materials, using bittern as raw material to prepare magnesium hydroxide whiskers, and then regulating the surface composition by a hydrothermal method to obtain a magnesium flame retardant whisker containing multiple catalytically active metal elements. The present invention adopts the above-mentioned method for preparing a magnesium flame retardant whisker containing multiple metal elements and its application, by growing double metal hydroxides on the surface of magnesium hydroxide whiskers, enhancing the interlocking effect of the interface between whiskers and resin, and improving the tensile strength of polymer composite materials, and the flame retardant synergist obtained by the invention enhances its heat reduction, smoke suppression and toxicity reduction effects through adsorption elimination, efficient catalytic carbonization and other effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant materials, in particular to a preparation method of magnesium flame retardant whiskers containing multiple metal elements and application thereof. Background Art

[0002] my country has a long coastline and rich coastal marine resources, including very rich sea salt resources. However, the rich sea salt resources are accompanied by a large amount of bittern byproduct emissions. Therefore, the rational and efficient development of magnesium resources in bittern can be used as a breakthrough for the comprehensive utilization of seawater bittern.

[0003] Magnesium hydroxide flame retardant does not produce toxic gases when burning, and can effectively inhibit the release of toxic and harmful smoke when polymer materials burn. It has multiple functions such as green environmental protection, flame retardant, low smoke and low toxicity. At the same time, magnesium hydroxide whiskers have a mechanical reinforcement effect on polymers, which improves the fire safety of polymers while effectively enhancing the tensile strength of polymers. Therefore, magnesium chloride resources can be extracted based on seawater bittern to prepare magnesium hydroxide whisker flame retardants. However, traditional magnesium hydroxide flame retardants are less efficient and must be added in large quantities to achieve a certain flame retardant level for polyolefins, unsaturated polyesters, etc., and large-scale additions lead to increased resin viscosity and decreased processing performance. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a magnesium-based flame retardant whisker containing multiple metal elements and its application, so as to solve the problems in the background technology.

[0005] To achieve the above object, the present invention provides a method for preparing magnesium flame retardant whiskers containing multiple metal elements, comprising the following steps:

[0006] S1. Take bittern from seawater, add excess alkali solution until precipitation is complete, filter to obtain a precipitate, disperse the precipitate in water, add an appropriate amount of hydrochloric acid until the precipitate is completely dissolved, and dry to obtain magnesium chloride;

[0007] S2, prepare magnesium chloride into a solution and place it in a flask, heat it to a certain temperature and then add ammonia water dropwise with stirring, stir and react for a period of time after the addition is complete, age it after the reaction is complete, filter and wash it, dry it, and grind it to obtain powder A;

[0008] S3, dispersing powder A in anhydrous ethanol, adding sodium hydroxide solution rapidly under slow stirring, reacting for a period of time, filtering, washing, drying, and grinding to obtain powder B;

[0009] S4. Powder B, aluminum sulfate 18hydrate and urea are dissolved in deionized water to obtain a mixed solution, and the mixed solution is added to a tetrafluoroethylene liner and mixed evenly. After mixing evenly, the liner is placed in a reactor, reacted at high temperature, naturally cooled, filtered, washed, and dried to obtain the final product, flame retardant whiskers.

[0010] Preferably, in S1, the alkali solution is a mixed solution of one or more of sodium hydroxide, ammonia water and sodium carbonate.

[0011] Preferably, in S2, the temperature for dropping ammonia water is 40-60°C, the heating method is water bath heating, the stirring reaction time is 1-2 h, the aging time is 24-48 h, and the aging temperature is 40-60°C.

[0012] Preferably, in S2, the temperature for dripping ammonia water is 50°C, the heating method is water bath heating, the stirring reaction time is 1.5 h, the aging time is 48 h, and the aging temperature is 50°C.

[0013] Preferably, in S3, the temperature for adding sodium hydroxide is 50-60° C., and the reaction time is 1-2 h.

[0014] Preferably, in S3, the temperature for adding sodium hydroxide is 60° C. and the reaction time is 1 h.

[0015] Preferably, in S4, one of magnesium sulfate heptahydrate, cobalt nitrate hexahydrate or copper sulfate pentahydrate is further added to the mixed solution.

[0016] Preferably, in S4, the mixing process is magnetic stirring at room temperature for 10 to 30 min, the reaction temperature of the reactor is 110 to 120° C., and the reaction time is 8 to 16 h.

[0017] Preferably, in S4, the mixing process is magnetic stirring at room temperature for 30 min, the reaction temperature of the reactor is 110° C., and the reaction time is 12 h.

[0018] Preferably, in S2-S4, the drying temperature is 80° C. and the drying condition is vacuum.

[0019] The present invention also provides a magnesium-based flame-retardant whisker containing multiple metal elements, which is prepared by the above-mentioned preparation method.

[0020] The present invention also provides an application of magnesium flame retardant whiskers containing multiple metal elements, and the prepared magnesium flame retardant whiskers are used as flame retardant synergists in flame retardant materials.

[0021] Preferably, the flame retardant material is prepared by mixing the final product prepared in the above preparation method S4 with the powder B prepared in S3 in a certain proportion, and adding one or more of polyolefin, unsaturated polyester and epoxy resin to prepare the flame retardant material.

[0022] Therefore, the preparation method of magnesium flame retardant whiskers containing multiple metal elements and the application thereof of the present invention have the following beneficial effects:

[0023] (1) In order to solve the technical problem of low flame retardant enhancement, smoke suppression and toxicity reduction efficiency of magnesium hydroxide whiskers, double hydroxide flakes were vertically grown on the surface of magnesium hydroxide whiskers through interface regulation to prepare flame retardant synergists containing multiple catalytically active metal elements. The flame retardant, smoke suppression and toxicity reduction effects of magnesium hydroxide whiskers were enhanced through adsorption elimination and efficient catalytic carbonization.

[0024] (2) In the present invention, after the double metal hydroxide grows vertically on the surface of the magnesium hydroxide whisker, the surface micro-nano pores enhance the interlocking effect between the whisker and the resin, thereby improving the tensile strength of the polymer composite material.

[0025] (3) The magnesium chloride solution for preparing the magnesium hydroxide whiskers in the present invention is prepared from bittern. After the magnesium hydroxide whiskers are prepared, the interface is further regulated to achieve the transformation of low-value bittern resources into high-value, high-performance flame retardants.

[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the XRD spectrum of powder B in Example 1 of the present invention;

[0028] Figure 2 is the IR spectrum of powder B in Example 1 of the present invention;

[0029] Figure 3 is a morphology diagram of powder B in Example 1 of the present invention;

[0030] Figure 4 is the XRD spectrum of the final product C in Example 1 of the present invention;

[0031] Figure 5 is the IR spectrum of the final product C in Example 1 of the present invention;

[0032] Figure 6 is a morphology diagram of the final product C in Example 1 of the present invention;

[0033] Figure 7 is a morphology diagram of the final product C in Example 2 of the present invention;

[0034] Figure 8 This is a comparison chart of combustion release inhibition between flame-retardant EVM / PE and pure EVM / PE in Application Example 1 of the present invention;

[0035] Fig. 9 This is a comparison chart of total heat release between flame-retardant EVM / PE and pure EVM / PE in Application Example 1 of the present invention;

[0036] Fig.10This is a comparison chart of combustion release inhibition between flame-retardant EVM / PE and pure EVM / PE in Application Example 2 of the present invention;

[0037] Fig.11 This is a comparison chart of total heat release between flame-retardant EVM / PE and pure EVM / PE in Application Example 2 of the present invention;

[0038] Fig.12 This is a comparison chart of combustion release inhibition between flame-retardant EVM / PE and pure EVM / PE in Application Example 3 of the present invention;

[0039] Fig.13 This is a comparison chart of total heat release between flame-retardant EVM / PE and pure EVM / PE in Application Example 3 of the present invention;

[0040] Fig.14 This is a comparison chart of the combustion release inhibition of the flame-retardant EVM / PE and pure EVM / PE in the comparative example 1 of the present invention and the flame-retardant EVM / PE in the application example 1;

[0041] Fig.15 This is a comparison chart of total heat release between the flame-retardant EVM / PE and pure EVM / PE in comparative example 1 of the present invention and the flame-retardant EVM / PE in application example 1;

[0042] Fig.16 This is a comparison chart of the combustion release inhibition of the flame-retardant EVM / PE and pure EVM / PE in the comparative example 2 of the present invention and the flame-retardant EVM / PE in the application example 1;

[0043] Fig.17 This is a comparison chart of total heat release between the flame-retardant EVM / PE and pure EVM / PE in Application Comparative Example 2 of the present invention, and the flame-retardant EVM / PE in Application Example 1. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0045] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0046] Example 1

[0047] In this embodiment 1, a magnesium hydroxide whisker is prepared, which specifically comprises the following steps:

[0048] S1. Take seawater bittern, add activated carbon for adsorption and decolorization, then add excess sodium hydroxide solution (the molar ratio of magnesium ions to alkali solution is 1:2.1) until precipitation is complete; filter the precipitate and retain the precipitate product, disperse the precipitate in water, pass an appropriate amount of hydrochloric acid (pH controlled at 7.0~7.5) until the precipitate is completely dissolved, and then dry the water in an oven to obtain a magnesium chloride product;

[0049] S2. Prepare 33.324 g of magnesium chloride into a 3.5 mol / L solution, place it in a three-necked round-bottom flask, and add 4.7 g of 25 wt% ammonia water dropwise under constant temperature stirring in a 50°C water bath; after the addition is completed, stir vigorously for 1.5 h; then age at 50°C for 48 h; filter and wash the aged product, vacuum dry it at 80°C, and grind it to obtain a white foamy powder A;

[0050] S3. Take 1.32 g of powder A and disperse it in 100 ml of anhydrous ethanol. Add 3 ml of 3.5 mol / L NaOH solution quickly under slow stirring at 60°C and react for 1 hour. Obtain white foamy powder B by suction filtration, washing, vacuum drying at 80°C and grinding.

[0051] S4. Dissolve 1 g of powder B, 0.436 g of magnesium sulfate heptahydrate, 0.2 g of aluminum sulfate 18hydrate, and 1.297 g of urea in 50 mL of deionized water, then slowly add the solution into a 100 ml tetrafluoroethylene liner, and stir magnetically at room temperature for 30 min to mix it thoroughly; put the liner into a reactor, react at 110°C for 12 h, cool naturally, filter and wash, and vacuum dry at 80°C to obtain product C.

[0052] The powder B and product C in Example 1 were tested respectively. Figure 1-Figure 6 shown.

[0053] Example 2

[0054] S1. Take seawater bittern, add activated carbon for adsorption and decolorization, then add excess sodium hydroxide and ammonia mixed solution (the molar ratio of magnesium ions to alkali solution is 1:2.1) until precipitation is complete; filter the precipitate and retain the precipitate product, disperse the precipitate in water, pass an appropriate amount of hydrochloric acid (pH controlled at 7.0~7.5) until the precipitate is completely dissolved, and then dry the water in an oven to obtain a magnesium chloride product;

[0055] S2. Prepare 33.324 g of magnesium chloride into a 3.5 mol / L solution, place it in a three-necked round-bottom flask, and add 4.7 g of 25wt% ammonia water dropwise in a 50°C water bath with constant temperature stirring; after the addition is completed, stir vigorously for 1.5 h; then age at 50°C for 48 h; filter and wash the aged product, vacuum dry it at 80°C, and grind it to obtain a white foamy powder A.

[0056] S3. Take 1.32 g of powder A and disperse it in 100 ml of anhydrous ethanol. Add 3 ml of 3.5 mol / L NaOH solution quickly under slow stirring at 60°C and react for 1 h. Obtain white foamy powder B by suction filtration, washing, vacuum drying at 80°C and grinding.

[0057] S4. Dissolve 1 g of powder B, 0.542 g of cobalt nitrate hexahydrate, 0.2 g of aluminum sulfate 18hydrate, and 1.297 g of urea in 50 mL of deionized water, then slowly add the solution into a 100 ml tetrafluoroethylene liner, and stir magnetically for 30 min at room temperature to mix it thoroughly; put the liner into a reactor, react at 110°C for 12 h, cool naturally, filter and wash, and vacuum dry at 80°C to obtain product C.

[0058] The morphology of the product C in Example 2 was detected using a cold field emission scanning electron microscope. Figure 7 shown.

[0059] Example 3

[0060] S1. Take seawater bittern, add activated carbon for adsorption and decolorization, then add excess sodium carbonate solution (the molar ratio of magnesium ion and sodium carbonate is 1:1.1) until precipitation is complete, filter the precipitate and retain the precipitate product, disperse the precipitate in water, pass an appropriate amount of hydrochloric acid (pH controlled at 7.0~7.5) until the precipitate is completely dissolved, and then dry the water in an oven to obtain magnesium chloride product.

[0061] S2. Prepare 33.324 g of magnesium chloride into a 3.5 mol / L solution, place it in a three-necked round-bottom flask, and add 4.7 g of 25ωt% ammonia water dropwise in a 50°C water bath with constant temperature stirring; after the addition is completed, stir vigorously for 1.5 h; then age at 50°C for 48 h, filter and wash the aged product, vacuum dry it at 80°C, and grind it to obtain a white foamy powder A.

[0062] S3. Disperse 1.32 g of powder in 100 ml of anhydrous ethanol, add 3 ml of 3.5 mol / L NaOH solution quickly under slow stirring at 60°C, and react for 1 hour; obtain white foamy powder B by suction filtration, washing, vacuum drying at 80°C, and grinding.

[0063] S4, 1 g powder B, 0.45 g copper sulfate pentahydrate, 0.2 g aluminum sulfate 18hydrate, 1.297 g urea were dissolved in 50 mL deionized water, and then the solution was slowly added to a 100 ml tetrafluoroethylene liner, and magnetically stirred for 30 min at room temperature to fully mix; the liner was placed in a reactor and reacted at 110 ° C for 12 h. Natural cooling, filtration and washing, and vacuum drying at 80 ° C were performed to obtain product C.

[0064] The products in the above-mentioned Examples 1-3 are applied to prepare flame retardant materials.

[0065] Application Example 1

[0066] 1) Add 24 parts of EVM700 and 24 parts of PE masterbatch into an internal mixer at 150°C and a screw speed of 60 rpm and melt mix for 5 minutes.

[0067] 2) Then, 50 parts of the powder B of the product of step S3 in Example 1 and 2 parts of the product of step S4 in Example 1 were added and kneaded for 8 minutes. After that, the mixture was hot-pressed at 165° C. for 8 minutes to obtain flame-retardant EVM / PE.

[0068] Taking pure EVM / PE as a comparison, the flame-retardant EVM / PE produced in Application Example 1 was tested for tensile strength, combustion heat release inhibition, total heat release inhibition and smoke inhibition, and its tensile strength is shown in Table 1 below:

[0069] Table 1 Tensile strength

[0070] ;

[0071] like Figure 8 As shown in the figure, compared with pure EVM / PE, the peak heat release rate of the flame retardant EVM / PE composite material with flame retardant synergist increased from 1176.0 kW / m 2 Down to 316.2 kW / m 2 .like Fig. 9 As shown in the figure, compared with pure EVM / PE, the total heat release of flame retardant EVM / PE is 105.5 MJ / m 2 Down to 71.4 MJ / m 2 In addition, compared with pure EVM / PE, the maximum optical density of the composite material with flame retardant synergist is reduced from 306.5 to 276.7.

[0072] Application Example 2

[0073] The raw material used in step 2) of Application Example 1 is replaced by the product prepared in Example 2 to obtain flame-retardant EVM / PE.

[0074] Taking pure EVM / PE as a comparison, the flame-retardant EVM / PE produced in Application Example 2 was tested for tensile strength, combustion heat release inhibition, total heat release inhibition, and smoke inhibition. The tensile strength is shown in Table 2 below:

[0075] Table 2 Tensile strength

[0076] ;

[0077] like Fig.10 As shown in Figure 2, compared with pure EVM / PE, the peak heat release rate of the composite material with flame retardant synergist increased from 1176.0 kW / m 2 Down to 344.4 kW / m 2 .like Fig.11 As shown in the figure, compared with pure EVM / PE, the total heat release of flame retardant EVM / PE is 105.5 MJ / m 2 Down to 77.0 MJ / m 2 In addition, compared with pure EVM / PE, the maximum optical density of the composite material with flame retardant synergist is reduced from 306.5 to 242.9.

[0078] Application Example 3

[0079] The raw material used in step 2) of Application Example 1 is replaced by the product prepared in Example 3 to obtain flame-retardant EVM / PE.

[0080] Taking pure EVM / PE as a comparison, the flame-retardant EVM / PE produced in Application Example 3 was tested for tensile strength, combustion heat release inhibition, total heat release inhibition, and smoke inhibition. The tensile strength is shown in Table 3 below:

[0081] Table 3 Tensile strength

[0082] ;

[0083] like Fig.12 As shown in the figure, compared with pure EVM / PE, the peak heat release rate of the flame retardant EVM / PE composite material with flame retardant synergist increased from 1176.0 kW / m 2 Down to 300.1 kW / m 2 .like Fig.13 As shown in the figure, compared with pure EVM / PE, the total heat release of flame retardant EVM / PE is 105.5 MJ / m 2 Down to 67.9 MJ / m 2 In addition, compared with pure EVM / PE, the maximum optical density of the composite material with flame retardant synergist is reduced from 306.5 to 219.2.

[0084] Application Comparative Example 1

[0085] 1) Add 24 parts of EVM700 and 24 parts of PE masterbatch into an internal mixer at 150°C and a screw speed of 60 rpm and melt mix for 5 minutes;

[0086] 2) Then, 52 parts of the ground product powder B of step S3 in Example 1 were added to obtain a product.

[0087] Taking pure EVM / PE as a comparison, the flame-retardant EVM / PE of the product in Application Comparative Example 1 and Application Example 1 was tested for tensile strength, combustion heat release inhibition, total heat release inhibition and smoke inhibition, and the tensile strength thereof is shown in Table 4 below:

[0088] Table 4 Tensile strength

[0089] ;

[0090] like Fig.14 As shown in the figure, compared with pure EVM / PE, the peak heat release rate of comparative example 1 is 1176.0 kW / m 2 Down to 346.4 kW / m 2 The peak heat release rate of Example 1 can be reduced to 316.2 kW / m 2 .like Fig.15 As shown in the figure, compared with pure EVM / PE, the total heat release of comparative example 1 is 105.5MJ / m 2 Down to 73.3 MJ / m 2 In Example 1, the total heat release can be reduced to 71.4 MJ / m 2 .

[0091] Application Comparative Example 2

[0092] The raw material used in step 2) of comparative example 1 was replaced with a commercially available magnesium hydroxide flame retardant to obtain flame-retardant EVM / PE.

[0093] Taking pure EVM / PE as a comparison, the flame retardant EVM / PE produced in Comparative Example 2 was tested for tensile strength, combustion heat release inhibition, total heat release inhibition and smoke inhibition, and its tensile strength is shown in Table 5 below:

[0094] Table 5 Tensile strength

[0095] ;

[0096] like Fig.16 As shown in the figure, compared with pure EVM / PE, the peak heat release rate of comparative example 2 is 1176.0 kW / m 2 Down to 331.5 kW / m 2 The peak heat release rate of Example 1 can be reduced to 316.2 kW / m2 .like Fig.17 As shown in the figure, compared with pure EVM / PE, the total heat release of comparative example 2 is 105.5 MJ / m 2 Down to 76.6 MJ / m 2 , while the total heat release of Example 1 can be reduced to 71.4 MJ / m 2 .

[0097] The vertical combustion and oxygen index of the above-mentioned application examples 1-3, application comparative example 1, application comparative example 2 and pure EVM / PE are compared, as shown in the following Table 6:

[0098] Table 6 Performance index

[0099] ;

[0100] The results show that the vertical combustion and oxygen index of flame retardant EVM / PE are significantly improved compared with pure EVM / PE. Compared with the comparative example, the vertical combustion and oxygen index of flame retardant EVM / PE in the embodiment are generally higher.

[0101] Therefore, the present invention provides a method for preparing magnesium-based flame-retardant whiskers containing multiple metal elements and their application, wherein double metal hydroxides are grown on the surface of magnesium hydroxide whiskers, and the micro-nano pores on the surface enhance the interlocking effect between the whiskers and the resin, thereby improving the tensile strength of the polymer composite material. The flame-retardant synergist obtained enhances its heat-reducing, smoke-suppressing and toxicity-reducing effects through adsorption elimination, efficient catalytic carbonization and the like.

[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing magnesium flame retardant whiskers containing multiple metal elements, characterized in that: The following steps are involved: S1. Take bittern from seawater, add excess alkali solution until precipitation is complete, filter to obtain a precipitated product, disperse the precipitated product in water, add an appropriate amount of hydrochloric acid until the precipitate is completely dissolved, and dry to obtain magnesium chloride, wherein the alkali solution is a mixed solution of one or more of sodium hydroxide, ammonia water, and sodium carbonate; S2, prepare magnesium chloride into a solution and place it in a flask, heat it to a certain temperature, then add ammonia water dropwise with stirring, the temperature of the ammonia water dropwise addition is 40-60°C, the heating method is water bath heating, the stirring reaction time is 1-2 h, after the dropwise addition is completed, stir the reaction for a period of time, after the reaction is completed, age it, the aging time is 24-48 h, the aging temperature is 40-60°C, filter it, wash it, dry it, and grind it to obtain powder A; S3, dispersing powder A in anhydrous ethanol, adding sodium hydroxide solution rapidly under slow stirring, reacting for a period of time, filtering, washing, drying, and grinding to obtain powder B; S4. Powder B, aluminum sulfate 18hydrate and urea are dissolved in deionized water to obtain a mixed solution. One of magnesium sulfate heptahydrate, cobalt nitrate hexahydrate or copper sulfate pentahydrate is also added to the mixed solution. The obtained mixed solution is added to a tetrafluoroethylene liner and mixed. The mixing process is magnetic stirring at room temperature for 10 to 30 min. After mixing, the liner is placed in a reactor for high-temperature reaction. The reaction temperature of the reactor is 110 to 120°C and the reaction time is 8 to 16 h. After natural cooling, it is filtered, washed, and dried to obtain the final product.

2. The method for preparing a magnesium flame retardant whisker containing multiple metal elements according to claim 1, characterized in that: In S3, the temperature for adding sodium hydroxide is 50-60° C., and the reaction time is 1-2 h.

3. The method for preparing a magnesium flame retardant whisker containing multiple metal elements according to claim 1, characterized in that: In S2-S4, the drying temperature is 80° C. and the drying condition is vacuum.

4. A magnesium flame retardant whisker containing multiple metal elements, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 3.

5. An application of magnesium flame retardant whiskers containing multiple metal elements, characterized in that: The magnesium flame retardant whisker prepared in claim 4 is used as a flame retardant synergist in a flame retardant material, the final product prepared in preparation method S4 is mixed with powder B prepared in S3 in a certain proportion, and one or more of polyolefins, unsaturated polyesters, and epoxy resins are added to prepare a flame retardant material.

Citation Information

Patent Citations

  • Method for preparing rod-like magnesium hydroxide from salt lake brine

    CN102674409A